Cohab/RN: o caminho da interiorização - Sara Raquel Fernandes Queiroz de Medeiros (Confins)
The housing policy implemented in Brazil by the Nacional Housing Bank (Banco Nacional de Habitação – BNH) included the Housing Companies (Companhias de Habitação – Cohabs) established in each federative state among its operating agencies. This paper looks at the actions carried out by Cohab/RN with respect to the construction of housing estates in the interior of the state and seeks to contribute to the research on housing outside of big urban centers. Different qualitative and quantitative data sources were used, such as institutional databases (for example, BHH, DATANORTE and IBGE), newspapers (Tribuna do Norte), and magazines (RN-econômico and BN em resumo), among others. The information was organized to prioritize a historic and spatial analysis, with data organized in tables, figures and maps. Political, economic and social motivations that contributed to the interiorization of Cohab/RN were highlighted, as well as the idiosyncrasies of this process. It is important to note that the analysis of these housing estates provides important elements to understand the local reality and/or comparative analyses regarding both the current housing policies in RN, and actions carried out by other Cohabs in Brazil.